Administrative management and staff turnover at the Office of the Attorney General, Portoviejo Canton, Manabí Province - Cabal Briones, Fernanda (2025)
Staff turnover in public institutions remains a challenge that affects both operational efficiency and organizational stability. The objective of this study is to analyze the administrative management factors that influence staff turnover at the Office of the Attorney General in Portoviejo, Manabí Province, Ecuador. A mixed-methods approach with an explanatory scope was employed, combining in-depth interviews with key Human Resources personnel and structured surveys administered to staff members of the Prosecutor's Office in Portoviejo. The analysis integrated qualitative techniques and descriptive statistics to identify factors associated with staff turnover. Findings revealed that, despite a solid organizational structure, human talent management shows weaknesses in recognition, motivation, and flexibility, which negatively impact employee commitment and contribute to turnover. A more strategic, well-being-centered approach is recommended to strengthen staff retention.